PENGEMBANGAN MEDIA PAPAN BERHITUNG BERBASIS METODE MONTESSORI PADA MATERI PENJUMLAHAN DAN PENGURANGAN BAGI SISWA KELAS I SD - S. Febrina Sri Mulyani; Andri Anugrahana (Universitas Tangerang Raya, 2023)
The aim of this study was to produce a counting board media based on the Montessori Method for first grade students in elementary school in addition and subtraction. The type of research used is research & development (R&D) with the Borg and Gall model. Media development includes 6 stages: research and data colletion, planning, develop preliminary form a product, preliminary field testing, final product revision,and dissemination and implementation. The subjects in this study were grade 1st students at Kanisius Wirobrajan Elementary School for the 2022/2023 academic year. The object of this research is learning media based on the Montessori method. Data collection techniques used were interviews, questionnaires, tests and observation. The data collection instruments used were interview guides, questionnaires, test questions and observation guidelines.The results of this study indicate: (1) The development of media based on the Montessori method is in accordance with the development steps according to Borg and Gall. (2)Product quality is in accordance with Montessori characteristics, namely interesting, graded, auto-correction, auto-education and contextual. Product quality that has been validated by Montessori and Mathematics Experts has “very good” quality with an average score of 3,91. (3) The development of Montessori method based counting board media is able to improve students’ ability to count addition and subtraction because it has increased by 112.9% and students become more active in the learning process.